2012
DOI: 10.1111/j.1540-6261.2012.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cross‐Border Mergers and Acquisitions

Abstract: The vast majority of cross-border mergers involve private firms outside of the United States. We analyze a sample of 56,978 cross-border mergers between 1990 and 2007. We find that geography, the quality of accounting disclosure, and bilateral trade increase the likelihood of mergers between two countries. Valuation appears to play a role in motivating mergers: firms in countries whose stock market has increased in value, whose currency has recently appreciated, and that have a relatively high market-to-book v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
436
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 668 publications
(513 citation statements)
references
References 51 publications
31
436
1
6
Order By: Relevance
“…A particular study that is in line with our research is Erel, Liao and Weisbach (2012), who employed a gravitational model at the country level and found that the geographical distance, the quality of accounting information, and the level of bilateral trade are among some of the determinants of M&As activity between two countries. Additionally, the authors argue that it is likely that institutional characteristics at the country level are positively correlated with better corporate governance.…”
Section: Corporate Governancementioning
confidence: 71%
See 1 more Smart Citation
“…A particular study that is in line with our research is Erel, Liao and Weisbach (2012), who employed a gravitational model at the country level and found that the geographical distance, the quality of accounting information, and the level of bilateral trade are among some of the determinants of M&As activity between two countries. Additionally, the authors argue that it is likely that institutional characteristics at the country level are positively correlated with better corporate governance.…”
Section: Corporate Governancementioning
confidence: 71%
“…Furthermore, the authors that have applied the gravitational model to transnationals M&As, have always done so at the country level (Di Giovanni 2005;Erel, Liao, and Weisbach 2012;Head and Ries 2008;Hyun and Kim 2010;Portes and Rey 2005). 1 Finally, we measure industry productivity for each factor of production.…”
mentioning
confidence: 99%
“…Bris and Cabolis (2008) further find that shareholder protection and accounting standards in the acquirer's country is positively related to the merger premium in cross-border M&As. Erel, Liao, and Weisbach (2012) extend their sample to include not only public firms but also private firms. They find that the likelihood of cross-border M&As is related to geography, the quality of accounting disclosure, bilateral trade, and stock valuation.…”
Section: Cross-border Mandasmentioning
confidence: 99%
“…Fourth, while previous studies use either Tobit or Ordinary Least Squares (OLS) regressions to examine the determinants of the volume and intensity of cross-border M&A activity (e.g., Rossi and Volpin, 2004;Ferreira et al, 2010;Erel, Liao, and Weisbach, 2012), I show that Zero-Inflated…”
mentioning
confidence: 99%
See 1 more Smart Citation